To be or not to be tetraploid—the impact of marker ploidy on genomic prediction and GWAS of potato - Aalborg, Trine; Nielsen, Kåre Lehmann (Frontiers in Plant Science, 2024)
Cultivated potato, Solanum tuberosum L., is considered an autotetraploid with 12 chromosomes with four homologous phases. However, recent evidence found that due to frequent large phase deletions in the genome, gene ploidy is not constant across the genome. The elite cultivar 'Otava' was found to have an average gene copy number of 3.2 across all loci. Breeding programs for elite potato cultivars rely increasingly on genomic prediction tools for selection breeding and elucidation of quantitative trait loci underpinning trait genetic variance. These are typically based on anonymous SNP markers, that are usually called from e.g. SNP array or sequencing data using a tetraploid model. In this study, we analyzed the impact of using whole genome markers genotyped as either tetraploid or observed allele frequencies from genotype-by-sequencing data on single-trait additive GBLUP GP models and single-marker regression GWAS of potato to evaluate the implications of capturing varying ploidy on the statistical models employed in genomic breeding. A panel of 762 offspring of a diallel cross of 18 parents of elite breeding material was used for modeling. These were genotyped by sequencing and phenotyped for five key performance traits: chipping quality, length/width ratio, senescence, dry matter content, and yield. We also estimated the read coverage required to confidently discriminate between a heterozygous triploid and tetraploid state from simulated data. It was found that using a tetraploid model neither impaired nor improved genomic predictions compared to using the observed allele frequencies that account for true marker ploidy. In GWAS, very minor variations of both signal amplitude and number of SNPs supporting both minor and major QTLs were observed between the two data sets. However, all major QTLs were reproducible using both data sets.